Paracloeodes caldensis (Ephemeroptera: Baetidae), an atypical new species from the Colombian Andes - Gutiérrez, Yeisson; Dias, Lucimar Gomes; Salles, Frederico Falcão (Zootaxa, 2013)
In the present work, an atypical new species of Paracloeodes Day (Ephemeroptera: Baetidae) is described based on nymphs collected in the Caldas Department, Central Cordillera of Colombia. This represents the first report of the genus from Colombia. The main characteristics that distinguish the new species from congeners are: abundant setae on femora, antennae length twice the width of the head capsule, maxilla with palp twice the length of the galea-lacinia, segment II of the labial palp with a rounded projection and 2.5 times the width of segment III, tarsal claws half the length of their respective tarsi and the abdominal color pattern. The concepts of the genera Paracloeodes, Varipes and Rivudiva are discussed in light of the discovery of P. caldensis n. sp.